Odpowiedzi

Najlepsza Odpowiedź!
2010-04-16T16:33:05+02:00
1. (x-2)² - 3x= (2x- 1)(2x+ 1)
x²-4x+4-3x=4x²-1
-3x²-7x+5=0
Δ=b²-4ac
trzeba wyliczyć deltę a poźniej x

2. x²+ mx- x+ 1= 0
x²+(m-1)x+1=0
Δ=b²-4ac
Δ=(m-1)²-4=m²-2m+1-4=m²-2m-3
m²-2m-3>0
m²-2m-3=0
Δ=b²-4ac
Δ=4+12=16
m1=(-b-√Δ)/2a
m1=(2-4)/2= -2/2=-1
m2=(-b+√Δ)/2a
m2=(2+4)/2= 6/2=3
parabola ramionami do góy m∈(-∞,-1)suma(3,+∞)

3. Rozwiąż nierówność
-x²+ 3x- 2 ≤ 0
-x²+ 3x- 2 =0
Δ=9-8=1
x1=(-b-√Δ)/2a
x1=(-3-1)/-2= -4/-2= 2
x2=(-b+√Δ)/2a
x2=(-3+1)/-2= -2/-2= 1
parabola ramionami do dołu x ∈(-∞,1> suma <2, +∞)